Tofacitinib in juvenile idiopathic arthritis: a double-blind, placebo-controlled, withdrawal phase 3 randomised trial. Issue 10315 (27th November 2021) - Ruperto, Nicolino; Brunner, Hermine I; Synoverska, Olga; Ting, Tracy V; Mendoza, Carlos Abud; Spindler, Alberto; Vyzhga, Yulia; Marzan, Katherine; Grebenkina, Lyudmila; Tirosh, Irit; Imundo, Lisa; Jerath, Rita; et al.
Summary: Background: Tofacitinib is an oral Janus kinase inhibitor. This trial assessed the efficacy and safety of tofacitinib versus placebo in patients with polyarticular course juvenile idiopathic arthritis (JIA). Methods: This double-blind, withdrawal phase 3 trial enrolled patients with polyarticular course JIA (extended oligoarthritis, rheumatoid factor-positive or rheumatoid factor-negative polyarthritis, or systemic JIA without active systemic features) aged 2 years to younger than 18 years, and was done at 64 centres of the Paediatric Rheumatology International Trials Organisation and Pediatric Rheumatology Collaborative Study Group networks in 14 countries. Patients with psoriatic arthritis or enthesitis-related arthritis were enrolled for exploratory endpoints. During part 1 of the study, patients received oral open-label tofacitinib (weight-based doses; 5 mg twice daily or lower) for 18 weeks. Patients achieving at least JIA/American College of Rheumatology 30 response were randomly assigned (1:1) using an Interactive Response Technology system to continue tofacitinib or switch to placebo in part 2 of the study for 26 weeks. The primary endpoint was JIA flare rate by week 44 in part 2 in patients with polyarticular course JIA; the intention-to-treat principle was applied. Safety was evaluated throughout part 1 and part 2 of the study in all patients who received one dose or more of study medication. This trial is registered with ClinicalTrials.gov, NCT02592434 . Findings: Between June 10, 2016, and May 16, 2019, of 225 patients enrolled, 184 (82%) patients had polyarticular course JIA, 20 (9%) had psoriatic arthritis, and 21 (9%) had enthesitis-related arthritis. 147 (65%) of 225 patients received concomitant methotrexate. In part 2, 142 patients with polyarticular course JIA were assigned to tofacitinib (n=72) or placebo (n=70). Flare rate by week 44 was significantly lower with tofacitinib (21 [29%] of 72 patients) than with placebo (37 [53%] of 70 patients; hazard ratio 0·46, 95% CI 0·27–0·79; p=0·0031). In part 2 of the study, adverse events occurred in 68 (77%) of 88 patients receiving tofacitinib and 63 (74%) of 85 in the placebo group. Serious adverse events occurred in one (1%) and two (2%), respectively. In the entire tofacitinib exposure period, 107 (48%) of 225 patients had infections or infestations. There were no deaths during this study. Interpretation: The results of this pivotal trial show that tofacitinib is an effective treatment in patients with polyarticular course JIA. New oral therapies are particularly relevant for children and adolescents, who might prefer to avoid injections. Funding: Pfizer.